2010
DOI: 10.1007/s10164-009-0199-z
|View full text |Cite
|
Sign up to set email alerts
|

Spatial properties of a forest buffalo herd and individual positioning as a response to environmental cues and social behaviour

Abstract: Many animals aggregate into organized temporary or stable groups under the influence of biotic and abiotic factors, and some studies have shown the influence of habitat features on animal aggregation. This study, conducted from 2002 to 2004 in the Dzanga-Ndoki National Park, Central African Republic, studied a herd of forest buffaloes (Syncerus caffer nanus) to determine whether spatial aggregation patterns varied by season and habitat. Our results show that both habitat structure and season influenced spatial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 55 publications
2
4
0
Order By: Relevance
“…A candidate tactic is the use of more peripheral and unoccupied patches in the natural conditions. Such a pattern has been observed in many social foragers (Hall and Fedigan 1997;Melletti et al 2010;Hirsch 2011), including our baboons (King et al 2009), Table 4). Values on the x-axes were standardized to have a mean of zero and standard deviation of one before model fitting.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…A candidate tactic is the use of more peripheral and unoccupied patches in the natural conditions. Such a pattern has been observed in many social foragers (Hall and Fedigan 1997;Melletti et al 2010;Hirsch 2011), including our baboons (King et al 2009), Table 4). Values on the x-axes were standardized to have a mean of zero and standard deviation of one before model fitting.…”
Section: Discussionsupporting
confidence: 72%
“…Such a pattern has been observed in many social foragers (Hall and Fedigan ; Melletti et al. ; Hirsch ), including our baboons (King et al. ), and would allow these individuals to reduce the foraging competition they experienced but also comes with costs such as increased predation risk and reduced access to social information (Hirsch ; Morrell and Romey ; Rieucau and Giraldeau ).…”
Section: Discussionsupporting
confidence: 54%
“…An individual's position on this competitionpredation gradient tends to be determined by its competitive ability. In species such as ringtailed coatis, Nasua nasua, and forest buffalo, Syncerus caffer nanus, adult males tend to occupy central positions whereas juveniles tend to be on the periphery (Melletti et al 2010;Hirsch 2011). However, in species with more complex intragroup social structures, competitive ability (and so spatial position) tends to be determined by factors such as rank (chacma baboons, Papio ursinus, Cowlishaw 1999; capuchin monkeys, Di Bitetti & Janson 2001; see 'Social Environment' below).…”
Section: Individual Traitsmentioning
confidence: 99%
“…This may be due to the abundance of food sources in the GL as compared with the dry season. Individuals of forest buffaloes distributed themselves in a more aggregated spatial pattern when resting in clearings than in forest (Melletti et al ., , ). Korte () also reported that forest buffaloes depend on open habitat adjacent to continuous forest for resting.…”
Section: Discussionmentioning
confidence: 99%